Correlation of Shoulder Pain on Disability and Health Related Quality of Life Among Patients Attending Physiotherapy and Orthopedic Outpatient Departments of a Tertiary Hospital - Bimali, Inosha; Shrestha, Preju Sama; Kandel, Binay (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Introduction: Shoulder pain is one of the common musculoskeletal conditions that substantially impact health related quality of life (HRQOL) and results in significant morbidity and disability. Understanding the interplay between pain, disability and HRQOL is crucial for clinicians to comprehend prognosis and evaluate treatment efficacy. Therefore, this study aimed to explore the relationship between shoulder pain, disability and HRQOL. Method: Patients aged 18-60 years with chronic shoulder pain (>3 months) were recruited from the outpatient department of physiotherapy and orthopedics. Data was collected using the Nepali versions of Shoulder pain and disability Index (SPADI-NP) and World Health Organization Quality of Life Questionnaire (WHOQOL-BREF). Statistical analysis included descriptive statistics to summarize the data characteristics, and Pearson correlation analysis to assess relationships between shoulder pain, disability and HRQOL. Results: Among the 96 participants, the mean SPADI-NP score was 72.12±16. The psychological domain (48.34±12.03) was most affected domain of HRQOL, followed by physical domain (50.34±13.48) in WHOQOL-BREF. Significant correlations were found between pain and disability (r=0.662, P<0.01), pain and HRQOL (r=-0.267, P<0.01), and disability and HRQOL (r=-0.493, P<0.01) respectively. Conclusion: This study identified significant relationships between shoulder pain, disability and HRQOL, emphasizing an importance of implementation of biopsychosocial approach for comprehensive treatment and better patient outcomes in those with shoulder pain.